Prevalence of psychiatric co morbidities in bronchial asthma and chronic obstructive pulmonary disease patients in north Indian population cohort - Mahajan, Vineet; Sareen, Himanshu; Kant, Surya; Bajpai, Jyoti; Narain, Apoorva; Soni, Sandeep; Kapoor, B. K. (International Journal of Research in Medical Sciences, 2018)
Background: Psychiatric co morbidities tend to occur quite frequently in patients of chronic respiratory diseases mainly bronchial asthma and Chronic Obstructive Pulmonary Disease (COPD) but still it is highly under diagnosed. Aim and objective of the study was to find out the prevalence of psychiatric co morbidities in asthma and COPD and to correlate them with disease severity according to Global Initiative against Obstructive Lung Disease (GOLD) and Global Initiative against Asthma (GINA) guidelines. Methods: Study was conducted in Department of TB and Chest in association with Department of Psychiatry of Punjab Institute of Medical Sciences, a secondary care medical college in north India. A total 204 patients, 68 of bronchial asthma, 68 0f COPD and 68 were controls included in the study. Diagnosis and severity of respiratory diseases was assessed by spirometry. Evaluation of psychiatric co morbidities was done using the MINI international neuropsychiatric interview questionnaire. Results: The frequency of psychiatric co morbidities in COPD patients was significantly higher (32.4%) compared to patients of bronchial asthma (20.6%). The most common co morbidity in both arms was generalized anxiety disorder (17.6% in COPD patients and 10.3% in patients of bronchial asthma. Conclusions: COPD patients have a higher frequency of psychiatric co morbidities compared to bronchial asthma patients and control population. These should be properly screened and treated.